Testing new physics in long baseline neutrino oscillation experiments - Díaz Desposorio, Félix Napoleón (Pontificia Universidad Católica del Perú, 2023)
In this thesis, we focus on analyzing the different ways in which new physics scenarios, such as Violation of the Equivalence Principle (VEP) and Quantum Decoherence, can manifest themselves in the context of the neutrino oscillation phenomenon. Within the framework of the DUNE experiment, we examine several effects of the VEP, such as the possibility of getting a misconstructed neutrino oscillation parameter region provoked by our ignorance of VEP in nature, as well as the impact on the DUNE sensitivity for CPV and mass hierarchy. Additionally, we set limits for the different textures of the gravitational matrix and the diverse scenarios of energy dependencies associated with the Lorentz Violation. On the other hand, we demonstrate that the quantum decoherence phenomenon applied to the neutrino system leads us to fascinating phenomenological scenarios. One of the scenarios analyzed, within the context of quantum decoherence, is the one that breaks the fundamental CPT symmetry. For the latter, we identify what textures that include certain nondiagonal elements of the decoherence matrix are necessary. In this line, we propose a way to measure the CPT violation in the DUNE experiment using the muon neutrino and antineutrino channels for different energy dependencies. Another intriguing effect of considering the neutrino as an open quantum system is the possibility of discovering the neutrino nature by measuring the Majorana phase at the DUNE experiment achieving a competitive precision. As a consequence of the latter, we find that the crucial measurement of the CP violation phase (δCP), planned to be performed at the DUNE experiment, can be spoiled by the introduction of the decoherence and the Majorana phases in nature. Thus, a signature of a non-null Majorana phase is a sizable distortion in the measurement of the Dirac CP violation phase δCP at DUNE when compared with T2HK measurement. Subsequently, via simulation, we measured the Majorana phase for values of ϕ1/π = ±0.5 and decoherence parameter Γ = 4.5(5.5) × 10−24GeV, reaching a precision of 23 (21) %. This precision is consistent with the corresponding to the Dirac CP phase at T2K experiment.

En la presente tesis, nos enfocamos en analizar las diferentes formas en que los escenarios de física nueva, como la Violación del Principio de Equivalencia (VEP) y la Decoherencia Cuántica, pueden manifestarse en el contexto del fenómeno de oscilación de neutrinos. En el marco del experimento DUNE, examinamos distintos efectos de VEP, como la posibilidad de obtener una región de parámetros de oscilación de neutrinos mal construida debido a no considerar VEP en la naturaleza, el impacto en la sensitividad del experimento DUNE para CPV y la determinación de la jerarquía de masas. Adicionalmente, establecemos límites para las diferentes texturas de la matriz gravitacional y los diversos escenarios con distintas dependencias energéticas asociadas a la Violación de Lorentz. Por otro lado, demostramos que el fenómeno de la decoherencia cuántica aplicado al sistema de neutrinos nos conduce a fascinantes escenarios fenomenológicos. Uno de los escenarios analizados, dentro del contexto de la decoherencia cuántica, es el de la ruptura de la simetría fundamental CPT. Para esto último, identificamos que son necesarias texturas que incluyan ciertos elementos no diagonales de la matriz de decoherencia. En esta línea, proponemos una forma de medir la violación de CPT en el experimento DUNE utilizando los canales de neutrinos y antineutrinos muónicos para diferentes dependencias energéticas. Otro efecto interesante de considerar al neutrino como un sistema cuántico abierto es la posibilidad de descubrir la naturaleza del neutrino midiendo la fase de Majorana en el experimento DUNE con una precisión competitiva. Como consecuencia de lo último, encontramos que la medición de la fase de violación de CP (δCP), planificada para realizarse en el experimento DUNE, puede verse afectada por la introducción de la decoherencia y las fases de Majorana en la naturaleza. Por lo tanto, en el marco de la decoherencia, mostramos que una señal de una fase de Majorana no nula, es la observación de una distorsión considerable en la medición de la fase de violación CP δCP en DUNE en comparación con la medición realizada por T2HK. Posteriormente, mediante simulación, medimos la fase Majorana para valores de ϕ1/π = ±0.5 y el parámetro de decoherencia Γ = 4.5(5.5) × 10−24GeV, alcanzando una precisión de 23 (21) %. Esta precisión es consistente con la medida correspondiente a la fase CP de Dirac en el experimento T2K.
Keywords: Neutrinos; Oscilaciones; https://purl.org/pe-repo/ocde/ford#1.03.00